KESEHATAN MENTAL REMAJA TERKAIT RESIKO PENULARAN HIV-AIDS (ANALISIS SEMIOTIKA PADA IKLAN LAYANAN MASYARAKAT) - M Ravii Marwan (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study is to analyze public service advertisements related to HIV AIDS, the target is the community and especially for teenagers. This study uses a qualitative method which is carried out by carrying out describing activities, interpreting activities and also explaining a form of meaning from connotations in public service advertisements. In the semiotic analysis method in visual communication, it can be used for visual data analysis methods and also verbal data as a method in reading public service advertisements in viewing various forms of perspective ranging from culture, art, visual communication design as well as social and language.